Precision study of the η→μ+μ−γ and ω→μ+μ−π0 electromagnetic transition form-factors and of the ρ→μ+μ− line shape in NA60 - Arnaldi, Roberta; Banicz, Karoly; Specht, Hans Joachim (Physics letters, 2016)
The NA60 experiment studied low-mass muon pair production in proton-nucleus (p-A) collisions using a 400 GeV proton beam at the CERN SPS. The low-mass dimuon spectrum is well described by the superposition of the two-body and Dalitz decays of the light neutral mesons η, ρ, ω, η′ and ϕ, and no evidence of in-medium effects is found. A new high-precision measurement of the electromagnetic transition form factors of the η and ω was performed, profiting from a 10 times larger data sample than the peripheral In-In sample previously collected by NA60. Using the pole-parameterisation |F(M)|2=(1−M2/Λ2)−2 we find Λη−2=1.934±0.067 (stat.) ±0.050 (syst.) (GeV/c2)−2 and Λω−2=2.223±0.026 (stat.) ±0.037 (syst.) (GeV/c2)−2. An improved value of the branching ratio of the Dalitz decay ω→μ+μ−π0 is also obtained, with BR(ω→μ+μ−π0)=[1.41±0.09 (stat.)±0.15 (syst.)]×10−4. Further results refer to the ρ line shape and a new limit on ρ/ω interference in hadron interactions.
Im Titel sind "eta", "mu", "omega", "rho" und "pi" als griechische Buchstaben dargestellt
Im Titel sind "+", "-" und "0" hochgestellt
NA60 Collaboration: R. Arnaldi, K. Banicz, K. Borer, J. Castor, B. Chaurand, W. Chen, C. Cicalò, A. Colla, P. Cortese, S. Damjanovic, A. David, A. de Falco, A. Devaux, L. Ducroux, H. En'yo, J. Fargeix, A. Ferretti, M. Floris, A. Förster, P. Force, N. Guettet, A. Guichard, H. Gulkanian, J.M. Heuser, P. Jarron, M. Keil, L. Kluberg, Z. Li, C. Lourenço, J. Lozano, F. Manso, P. Martins, A. Masoni, A. Neves, H. Ohnishi, C. Oppedisano, P. Parracho, P. Pillot, T. Poghosyan, G. Puddu, E. Radermacher, P. Ramalhete, P. Rosinsky, E. Scomparin, J. Seixas, S. Serci, R. Shahoyan, P. Sonderegger, H.J. Specht, R. Tieulent, A. Uras, G. Usai, R. Veenhof, H.K. Wöhri
Gesehen am 19.08.2020